2017
DOI: 10.1186/s12872-016-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

The 100 most-cited articles on aortic dissection

Abstract: BackgroundTo identify and characterize the most frequently cited articles that have been published on aortic dissection.MethodsA list of the 100 most frequently cited publications (T100) about aortic dissection was generated by performing a searching of the Science Citation Index--Expanded using “aortic dissection” as the search term. Basic information about the articles was recorded, including number of citations, journal title, journal impact factor, time since publication, first author’s country, topic/subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
20
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
9
20
4
Order By: Relevance
“…In recent era, authors prefer speciality journals over general medical journals to publish their high‐quality articles. In the present study, we noted that most of the highly cited articles were published in relatively low IF (below 5) speciality journals, namely Journal of Oral Pathology and Medicine (57.89%) and Oral Oncology (28.94%), which is in agreement with previous reports . This demonstrates that the researchers follow these two journals most frequently for achieving information on OSF.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In recent era, authors prefer speciality journals over general medical journals to publish their high‐quality articles. In the present study, we noted that most of the highly cited articles were published in relatively low IF (below 5) speciality journals, namely Journal of Oral Pathology and Medicine (57.89%) and Oral Oncology (28.94%), which is in agreement with previous reports . This demonstrates that the researchers follow these two journals most frequently for achieving information on OSF.…”
Section: Discussionsupporting
confidence: 92%
“…Another reason for domination of these countries in research related to OSF could be the higher prevalence of OSF in Indian subcontinents & Asian countries . This observation of our study is in contrast with other studies which have shown higher contribution of USA due to their higher financial support to the researchers . In the present analysis, 5 articles from the United States appear in the top 100 list.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Journals with high impact factor are attracted by authors for deciding the journal that is submitted their manuscript [58]. Although the positive relationship is observed between the citations index and impact factor of the journals in the previous studies [63,64], in this study, there was only one article published in the journals with an impact factor of more than five. This journal was the American Journal of Surgical Pathology.…”
Section: Discussionmentioning
confidence: 53%